A novel nanomaterial baffle decrease aerosols and microbial aerosols during non-contact tonometry measurements - X. Shen; Y. Guo, X; X. Wang; Y. Ye; Q. Chi; W. Zhou; Y. Chen; C. Li (РМЖ "Клиническая офтальмология")
X. Shen, Y. Guo, X. Wang, Y. Ye, Q. Chi, W. Zhou, Y. Xu, P. Wu, H. Zhou, Y. Chen, C. Li, Y. Chen Wenzhou Medical University, Wenzhou, China Aim: to develop a novel baffle to decrease aerosols and microbial aerosols produced during non-contact tonometry (NCT) measurements. Materials and Methods: the cluster analysis performed by Autof Analyzer software contained in MALDI-TOF MS (Autof MS 600, Autobio, China) based on microbes detected in microbial aerosols samples during NCT measurements, in human conjunctiva samples, in the air and typical strains in the database. Overall, 1594 person-time were included. The participants randomly divided into groups: NCT with a novel antimicrobial aerosol nanocomposite baffle (Group 1), NCT with a plastic baffle (Group 2), NCT without a baffle (Group 3) and participants without NCT measurements (Background investigation). NCT measurements performed in Groups 1–3.We used Air quality detectors and Air Ideal® 3P to monitor and sample aerosols and microbial aerosols during NCT measurements. Blood agar plates (Bio-kont, China) were used in the microbial sampler with a diameter of 90 mm. The plates were kept in aerobic conditions at about 25°C for 3–5 days, then the colonies on the plates were counted. Results: Staphylococcus epidermidis from microbial aerosols samples cluster with those from human samples rather than those from air. Burkholderia spp. and other microbes tested in the microbial aerosols cluster with each other rather than those in the air. Aerosols and microbial aerosols in the background did not show stable accumulation effect nor upward trend. Compared with the increasing trend of aerosols and microbial aerosols in Group 2 and Group 3, those in Group 1 were low,and showing a significant downward trend. Conclusion: Aerosolized ocular surface microorganisms (AOSM) can spread by human eyes NCT measured, pathogens may among them. The effect of plastic baffle was beneficial but volatile. Antimicrobial aerosol nano-composite baffle can effectively reduce aerosols and microbial aerosols during NCT measurements. Keywords: Baffle, Bio-aerosols, Global human health, Nanocomposites, Non-contact tonometer, COVID-19, Infection surveillance and control, Glaucoma, Cornea, Sampling method. For citation: Shen X., Guo Y., Wang X., Ye Y., Chi Q., Zhou W., Xu Y., Wu P., Zhou H., Chen Y., Li C., Chen Y. A novel nanomaterial baffle decrease aerosols and microbial aerosols during non-contact tonometry measurements. Russian Journal of Clinical Ophthalmology. 2024;24(4):217–221 (in Russ.). DOI: 10.32364/2311-7729-2024-24-4-9